IMPLEMENTASI PROGRAM UANG ELEKTRONIK SEBAGAI ALAT PEMBAYARAN PADA BUS TRANS SEMARANG - Adela Putri L. Tobing; Dewi Rostyaningsih; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The government through BLU UPTD Trans Semarang launched the Electronic Money Program to encourage the acceleration of the transaction electronification program in local governments, especially Semarang City. One of the targets in this program is Trans Semarang Bus users who use cashless payments. The purpose of this study is to analyze how the implementation of the Electronic Money Program on the Trans Semarang Bus. This research is a research with descriptive qualitative methods. Data is obtained through two sources, namely primary data and secondary data. Data collection techniques include interviews, observations, and documentation. The focus of this research was studied using 5 criteria for successful implementation according to Cole, Martin, and Parston (in Erwan Agus Purwanto, 2015: 105). The results of research in the field show that the Implementation of the Electronic Money Program on the Trans Semarang Bus, namely, (a) Access to the Implementation of the Electronic Money Program as a Payment Tool on the Trans Semarang Bus, has not run optimally, due to an error system in electronic payment transaction instruments, (b) Service provisions in the Implementation of the Electronic Money Program as a Payment Instrument on the Trans Semarang Bus, have not run optimally, because they are found to be jostling in making electronic money transactions using QR barcode scans, (c) The suitability of the program in the Implementation of the Electronic Money Program as a Payment Instrument on the Trans Semarang Bus, has not run optimally, because there is no compelling policy, in the use of electronic money on the Trans Semarang Bus.